Analysis of the Learning Environment and Teacher-Student Interaction in Learning Dynamics at MA Assohwah Al-Islamiyah - Rejeki, Sri; Aulia, Al- Vina; Mujizat, Anisatul; Ramadhani, Imsak; Lutfia, Nayla; Arsyad, Lalu M. Ridho; Ningsih, Firda; Johansyah, Johansyah; Nugraha, Rifqi Ardhan (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This article is the result of observations conducted during the School Field Introduction Program (PLP) 1 at MA Assohwah Al-Islamiyah, which lasted for ten days. The aim of the study is to analyze the learning environment, teacher-student interactions, and the learning dynamics that occur. The method used was participatory observation, with data collection through field notes, informal interviews, and photographic documentation. The observation results show a generally conducive learning environment, characterized by adequate facilities and a relatively quiet classroom atmosphere. Teacher-student interactions are considered positive, with teachers tending to be communicative and students actively responding. Learning dynamics vary, with some teachers employing interactive and participatory learning methods, while others still use lecture methods. In conclusion, MA Assohwah Al-Islamiyah has the potential to improve the quality of learning by more consistently implementing active learning methods and increasing student engagement. Keywords: Learning Environment, Teacher-Student Interaction, Learning Dynamics, MA Assohwah Al-Islamiyah, School Field Introduction Program (PLP). Abstrak: Artikel ini merupakan hasil observasi selama Program Pengenalan Lapangan Persekolahan (PLP) 1 di MA Assohwah Al-Islamiyah yang berlangsung selama sepuluh hari. Tujuannya adalah untuk menganalisis lingkungan belajar, interaksi guru-siswa, dan dinamika pembelajaran yang terjadi. Metode yang digunakan adalah observasi partisipatif, dengan pengumpulan data melalui catatan lapangan, wawancara informal, dan dokumentasi foto. Hasil observasi menunjukkan lingkungan belajar yang umumnya kondusif, ditandai dengan fasilitas yang memadai dan suasana kelas yang relatif tenang. Interaksi guru-siswa tergolong positif, dengan guru yang cenderung komunikatif dan siswa yang aktif merespons. Dinamika pembelajaran bervariasi, dengan beberapa guru menggunakan metode pembelajaran yang interaktif dan partisipatif, sementara yang lain masih menggunakan metode ceramah. Kesimpulannya, MA Assohwah Al-Islamiyah memiliki potensi untuk meningkatkan kualitas pembelajaran dengan lebih konsisten menerapkan metode pembelajaran aktif dan meningkatkan keterlibatan siswa. Kata Kunci: Lingkungan Belajar, Interaksi Guru-Siswa, Dinamika Pembelajaran, MA Assohwah Al-Islamiyah, Program Pengenalan Lapangan Persekolahan (PLP).